2014
DOI: 10.4172/2157-7110.1000377
|View full text |Cite
|
Sign up to set email alerts
|

Sensory, Physical and Nutritional Qualities of Cookies Prepared from Pearl Millet (Pennisetum Typhoideum)

Abstract: Refined wheat flour, a key ingredient in cookie is mainly composed of starch which is devoid of nutrients particularly minerals. This study determines the possibility of using two different pearl millet varieties K & MRB (K and Maharashtra Rabi Bajra respectively) as a replacement for refined wheat flour in cookie preparation. Cookies were evaluated for proximate composition, textural and sensory characteristics. Proximate composition revealed that pearl millet cookies had higher protein, ash and mineral (iron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Given the low moisture content associated with the thinness, biscuits are characteristically hard and crunchy, properties that are much appreciated upon eating. However, compared to fish products its nutritional content is very low, being widely prepared from cereal products, which have low protein content and essential amino acids like lysine as well as other micronutrients [18]. Such a product represents a useful means of supplementing the diet of any section of the people, especially to meet the requirement of protein to a greater extent.…”
Section: Introductionmentioning
confidence: 99%
“…Given the low moisture content associated with the thinness, biscuits are characteristically hard and crunchy, properties that are much appreciated upon eating. However, compared to fish products its nutritional content is very low, being widely prepared from cereal products, which have low protein content and essential amino acids like lysine as well as other micronutrients [18]. Such a product represents a useful means of supplementing the diet of any section of the people, especially to meet the requirement of protein to a greater extent.…”
Section: Introductionmentioning
confidence: 99%
“…Fat imparts tenderness and assists in texture improvement to the product, making it more palatable and acceptable to consumers. Florence et al [ 47 ] reported similar results.…”
Section: Resultsmentioning
confidence: 52%
“…Pearl millet is generally used in the preparation of various value-added food products such as cutlets, weaning food, vermicelli, instant beverage powder, biscuits, upma mixes, bread, cakes, muffins, roti/chapati, instant idli, dhokla, uthapam, kheer, extruded product, cookies, snack bar, beverages (appalu, Oshikundu) [6,10,32,53,54,[59][60][61][62][63][64][65][66].…”
Section: Food Products Prepared From Pearl Milletmentioning
confidence: 99%